1996
DOI: 10.1136/hrt.75.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Relation between symptoms and profiles of coronary artery blood flow velocities in patients with aortic valve stenosis: a study using transoesophageal Doppler echocardiography.

Abstract: Objective-To analyse profiles of coronary artery flow velocity at rest in patients with aortic stenosis and to determine whether changes of the coronary artery flow velocities are related to symptoms in patients with aortic stenosis. Design-A prospective study investigating the significance of aortic valve area, pressure gradient across the aortic valve, systolic left ventricular wall stress index, ejection fraction, and left ventricular mass index in the coronary flow velocity profile of aortic stenosis; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 28 publications
1
17
0
5
Order By: Relevance
“…4 Hyperemia is hindered by a series of unfavorable hemodynamic changes, including high LV cavity pressure, low coronary perfusion pressure, and increased extravascular compressive forces that lead to an increased minimal coronary resistance. 5 In addition, characteristic pathological changes that contribute to impair microvascular function have been described in the hypertrophied ventricle of patients with AS. These consist of perimyocytic fibrosis 6 and reduction in the number of resistance vessels per unit of weight.…”
mentioning
confidence: 99%
“…4 Hyperemia is hindered by a series of unfavorable hemodynamic changes, including high LV cavity pressure, low coronary perfusion pressure, and increased extravascular compressive forces that lead to an increased minimal coronary resistance. 5 In addition, characteristic pathological changes that contribute to impair microvascular function have been described in the hypertrophied ventricle of patients with AS. These consist of perimyocytic fibrosis 6 and reduction in the number of resistance vessels per unit of weight.…”
mentioning
confidence: 99%
“…3 Perimyocytic fibrosis 4 and reduction in the number of resistance vessels per unit weight 5 may contribute to the reduction in CVR in LVH secondary to hypertension and hypertrophic cardiomyopathy. However, recent work suggests that increased systolic impedance to coronary flow as a result of perivascular compression 6 and, most importantly, a reduction in diastolic perfusion 2 are the primary contributors to impairment of coronary microcirculatory function in AS, predominantly because of curtailment in maximal myocardial blood flow (MBF).…”
mentioning
confidence: 99%
“…It has been demonstrated that reversed systolic flow velocity compensated by enhanced diastolic flow velocity, as seen in this patient (Fig 4), is related to symptoms, such as angina or syncope, caused by the aortic stenosis. 9 The present patient's infarct was very unusual in view of the involvement of the left ventricular circumferential subendocardium. In patients with severe aortic stenosis and normal or nearly normal coronary arteriograms, myocardial infarction can result from factors other than atherosclerosis, such as coronary vasospasm or thromboembolism, including calcium embolization.…”
Section: Discussionmentioning
confidence: 99%